1970
DOI: 10.1042/bj1180667
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation in Bacillus subtilis. Correlation of biochemical events with morphological changes in asporogeneous mutants

Abstract: A comparison was made of morphological changes and successive, mainly biochemical, marker events for sporulation in 14 asporogenous mutants. The morphological and biochemical sequences are linked so that arrested development in one is accompanied by corresponding effects in the other. Thus mutants that fail to produce both protease and antibiotic do not progress beyond stage 0, formation of alkaline phosphatase appears to be associated with the transition from stage II to stage III and glucose dehydrogenase wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
0

Year Published

1973
1973
1991
1991

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 20 publications
4
91
0
Order By: Relevance
“…The biochemical properties of the mutants with respect to production of enzymes associated with earlier stages of sporulation (Waites et al, 1970) was as expected; the three mutants all produced serine protease, alkaline phosphatase and glucose dehydrogenase. However, one of the three mutants, 516, was also defective in DPA production (DPA production is a stage V event).…”
Section: Discussionmentioning
confidence: 77%
“…The biochemical properties of the mutants with respect to production of enzymes associated with earlier stages of sporulation (Waites et al, 1970) was as expected; the three mutants all produced serine protease, alkaline phosphatase and glucose dehydrogenase. However, one of the three mutants, 516, was also defective in DPA production (DPA production is a stage V event).…”
Section: Discussionmentioning
confidence: 77%
“…By electron microscopy, spo-54 was shown to be either a spu0 or a spu/ mutant since some cells were observed with slightly indented asymmetric septa. Various enzymes and compounds that are expressed at specific times during sporulation in B. subtilis (Waites et al, 1970) were tested in B. megateriurn QM B1551 to establish the kinetics of expression in this strain and to determine whether they might be used to help distinguish mutants blocked at specific stages during our characterization of the fusion mutants. In B. subtilis, alkaline phosphatase is expressed at t 2 , glucose dehydrogenase at t3 and DPA between t4 and t5 (Waites et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Synthesis of several enzymes such as alkaline phosphatase and glucose de hydrogenase begins during specific stages of sporulation in B. subtilis (Waites et al, 1970) and their synthesis has been used to help delineate mutants blocked at specific stages (Mandelstam & Errington, 1987;Sandman et al, 1987). Expression of these enzymes was tested in wild-type B. megaterium and compared to one of the mutants as shown in Fig.…”
Section: Enzyme Assaysmentioning
confidence: 99%
“…phosphate repressible) enzyme (Warren 1968). Examination of the morphological and biochemical properties of asporogenous mutants suggested that this increase in phosphatase activity during spore formation was sporulationspecific and that it might be associated with stage II (spore septum formation) of the sporulation process (Waites et al 1970;Coote 1972). Cytochemical studies have provided additional evidence for linking the appearance of alkaline phosphatase during sporulation with stage II (Glenn 1971).…”
Section: Introductionmentioning
confidence: 99%
“…Early blocked sporulation mutants (i.e. all stage 0 and stage I and most of stage II) fail to produce alkaline phosphatase (Waites et al 1970;Coote 1972) although they produce normal levels of phosphatase when starved of phosphate in the vegetative state (Glenn 1971).…”
Section: Introductionmentioning
confidence: 99%